2022
DOI: 10.1128/mbio.03510-21
|View full text |Cite
|
Sign up to set email alerts
|

Candidalysins Are a New Family of Cytolytic Fungal Peptide Toxins

Abstract: Pathogenic fungi kill an estimated 1.5 million people every year. Recently, we discovered that the fungal pathogen Candida albicans secretes a peptide toxin called candidalysin during mucosal infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 43 publications
(79 reference statements)
0
24
0
Order By: Relevance
“…This peptide is also called Ece1-III because it is produced as a third of the eight cleaved fragments of cell elongation 1 (Ece1) protein that is specifically expressed in the hypha [2]. The candidate peptide is supposedly amphipathic and consists of 31 amino acids containing hydrophobic amino acid assemblies on two α-helical structures [2,3]. To date, the bioactivity of candidalysin has been investigated from a variety of aspects, especially using an Ece1-deficient strain of C. albicans and the synthetic peptide.…”
Section: Introductionmentioning
confidence: 99%
“…This peptide is also called Ece1-III because it is produced as a third of the eight cleaved fragments of cell elongation 1 (Ece1) protein that is specifically expressed in the hypha [2]. The candidate peptide is supposedly amphipathic and consists of 31 amino acids containing hydrophobic amino acid assemblies on two α-helical structures [2,3]. To date, the bioactivity of candidalysin has been investigated from a variety of aspects, especially using an Ece1-deficient strain of C. albicans and the synthetic peptide.…”
Section: Introductionmentioning
confidence: 99%
“…Since candidalysin is a classic virulence factor that involves a strong host immune response, species that prefer a more commensal mode of existence are unlikely to exploit its potential to that extent [93]. In the case of C. auris, the ECE1 gene has not been detected in the genome and, according to current knowledge, this species does not produce candidalysin [92].…”
mentioning
confidence: 98%
“…Orthologs of candidalysin from C. albicans have also been found in C. dubliniensis and C. tropicalis [92]. Interestingly, studies on oral epithelial cells and artificial lipid membranes presented by Richardson et al [92] indicated that candidalysins produced by C. dubliniensis and C. tropicalis have stronger and faster cytolytic and immunostimulatory effects than candidalysin of C. albicans. Importantly, both species cause less damage to epithelial cells than C. albicans, which may be due to lower Ece1 production, processing, or secretion during contact with the host.…”
mentioning
confidence: 99%
See 2 more Smart Citations